2015
DOI: 10.1016/j.amsu.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Intramural oesophageal dissection as an unusual presentation of chest pain: A case report

Abstract: IntroductionIntramural oesophageal dissection (IOD) is a rare clinical condition and there is a paucity of information regarding the appropriate diagnosis and management. It is described as bleeding in the submucosal plane of the oesophagus, and has various documented causes.Presentation of caseWe report a case of a 73 year old female who developed IOD. She presented with severe chest pain. Subsequent imaging revealed IOD and haematoma formation. This was confirmed on oesophagogastroduodenoscopy (OGD). She was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…We believe that the frequency of hematomas has reduced owing to careful endoscopy procedures and less time required for performing them in recent times. Previous reports revealed that chest pain, dysphagia, and hemorrhage cause esophageal hematomas, and these hematomas spread extensively from the upper to the lower esophagus 5,7–9 . Moreover, an ulcer was formed in the process, but resolved on treatment after a few weeks 7,9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We believe that the frequency of hematomas has reduced owing to careful endoscopy procedures and less time required for performing them in recent times. Previous reports revealed that chest pain, dysphagia, and hemorrhage cause esophageal hematomas, and these hematomas spread extensively from the upper to the lower esophagus 5,7–9 . Moreover, an ulcer was formed in the process, but resolved on treatment after a few weeks 7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports revealed that chest pain, dysphagia, and hemorrhage cause esophageal hematomas, and these hematomas spread extensively from the upper to the lower esophagus. 5 , 7 , 8 , 9 Moreover, an ulcer was formed in the process, but resolved on treatment after a few weeks. 7 , 9 In the present cases, hemispherical and relatively small hematomas tended to develop at multiple sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations